An inverse boundary element method/genetic algorithm based approach for retrieval of multi-dimensional heat transfer coefficients within film cooling holes/slots - Silieti, M.; Divo, E.; Kassab, A. J. (Inverse problems in science and engineering, 2005)
An inverse methodology is developed as a means of determining heat transfer coefficient distributions in film cooling holes/slots. Thermal conditions are over-specified at exposed surfaces amenable to measurement, while the temperature and surface heat flux distributions are unknown at the film cooling hole/slot walls. The latter are determined in an iterative manner by solving an inverse problem whose objective is to adjust the film-cooling hole/slot wall temperatures and heat flux distributions until the temperature and heat fluxes at the measurement surfaces are matched in an overall heat conduction solution. The heat conduction problem is solved using boundary element methods, and the inverse problem is solved using a genetic algorithm. The resulting film coefficient distributions are fit to a correlation reflecting dependency on position, the Prandtl and Reynolds numbers.